Single-cell transcriptomic profile of satellite glial cells in trigeminal ganglion - Chu, Yanhao; Jia, Shilin; Xu, Ke; Liu, Qing; Mai, Lijia; Liu, Jiawei; Fan, Wenguo; Huang, Fang (Frontiers in Molecular Neuroscience, 2023)
Satellite glial cells (SGCs) play an important role in regulating the function of trigeminal ganglion (TG) neurons. Multiple mediators are involved in the bidirectional communication between SGCs and neurons in different physiological and pathological states. However, molecular insights into the transcript characteristics of SGCs are limited. Moreover, little is known about the heterogeneity of SGCs in TG, and a more in-depth understanding of the interactions between SGCs and neuron subtypes is needed. Here we show the single-cell RNA sequencing (scRNA-seq) profile of SGCs in TG under physiological conditions. Our results demonstrate TG includes nine types of cell clusters, such as neurons, SGCs, myeloid Schwann cells (mSCs), non-myeloid Schwann cells (nmSCs), immune cells, etc., and the corresponding markers are also presented. We reveal the signature gene expression of SGCs, mSCs and nmSCs in the TG, and analyze the ligand-receptor pairs between neuron subtypes and SGCs in the TG. In the heterogeneity analysis of SGCs, four SGCs subtypes are identified, including subtypes enriched for genes associated with extracellular matrix organization, immediate early genes, interferon beta, and cell adhesion molecules, respectively. Our data suggest the molecular characteristics, heterogeneity of SGCs, and bidirectional interactions between SGCs and neurons, providing a valuable resource for studying SGCs in the TG.